2020
DOI: 10.1016/j.cegh.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and risk factors of toxoplasmosis among children age ranged from 1 to 14 years referred to medical diagnostic laboratories in Southeast Iran

Abstract: Background: Toxoplasmosis is one of the most common protozoan diseases in both developing and developed countries. Human infection occurred by incidental ingestion of oocyst-contaminated food, water, soil or tissue of raw meat. Studies of infection in Iranian children are infrequent. In this study, we investigated seroprevalence, and risk factors of toxoplasmosis among children under 15 years old in Sistan and Baluchistan province, Southeastern Iran. Materials and methods: 869 sera samples were investigated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The most prevalent parasitic infection in humans is toxoplasmosis caused by ingestion of Toxoplasma gondii, which is usually found in soils (Du et al, 2012;Saki et al, 2017). However, Raissi et al (2020) found no significant relationship between geophagia and Toxoplasma gondii infection Southeast Iran. Kutalek et al (2010) also concluded that geophagia is not a cause of adult helminth infection.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent parasitic infection in humans is toxoplasmosis caused by ingestion of Toxoplasma gondii, which is usually found in soils (Du et al, 2012;Saki et al, 2017). However, Raissi et al (2020) found no significant relationship between geophagia and Toxoplasma gondii infection Southeast Iran. Kutalek et al (2010) also concluded that geophagia is not a cause of adult helminth infection.…”
Section: Discussionmentioning
confidence: 99%